Smart Delivery of Biomolecules Interfering with Peri-Implant Repair in Osteoporotic Rats - Paludetto, Laura Vidoto [UNESP] (2024)
Bisphosphonates are widely used for the treatment of postmenopausal osteoporosis; however, they cause several long-term side effects, necessitating the investigation of local ways to improve osseointegration in compromised bone tissue. The purpose of this study was to evaluate peri-implant bone repair using implants functionalized with zoledronic acid alone (OVX ZOL group, n = 11), zoledronic acid + teriparatide (OVX ZOL + TERI group, n = 11), and zoledronic acid + ruterpy (OVX ZOL + TERPY group, n = 11) compared to the control group (OVX CONV, n = 11). Analyses included computer-assisted microtomography, qualitative histologic analysis, and real-time PCR analysis. Histologically, all functionalized surfaces improved peri-implant repair, with the OVX ZOL + TERI group standing out. Similar results were found in computerized microtomography analysis. In real-time PCR analysis, however, the OVX ZOL and OVX ZOL + TERPY groups showed better results for bone formation, with the OVX ZOL + TERPY group standing out, while there were no statistical differences between the OVX CONV and OVX ZOL + TERI groups for the genes studied at 28 postoperative days. Nevertheless, all functionalized groups showed a reduced rate of bone resorption. In short, all surface functionalization groups outperformed the control group, with overall better results for the OVX ZOL + TERI group.